Zunajcelični membranski vezikli v transfuzijskih pripravkih-biologija in klinična pomembnost - Krstova Krajnc, Emilija (Zdravniški vestnik, 2015)
Extracellular membrane vesicles are fragments shed from plasma membranes off all cell types that are undergoing apoptosis or are being subjected to various types of stimulation or stress. Even in the process of programmed cell death (apoptosis), cell fall apart of varying size vesicles. They expose phosphatidylserine (PS) on the outer leaflet of their membrane, and bear surface membrane antigens reflecting their cellular origin. Extracellular membrane vesicles have been isolated from many types of biological fluids, including serum, cerebrospinal fluid, urine, saliva, tears and conditioned culture medium. Flow cytometry is one of the many different methodological approaches that have been used to analyze EMVs. The method attempts to characterize the EMVs cellular origin, size, population, number, and structure. EMVs are present and accumulate in blood products (erythrocytes, platelets) as well as in fresh frozen plasma during storage. The aim of this review is to highlight the importance of extracellular vesicles as a cell-to-cell communication system and the role in the pathogenesis of different diseases. Special emphasis will be given to the implication of extracellular membrane vesicles in blood products and their clinical relevance. Although our understanding of the role of EMVs in disease is far from comprehensive, they display promise as biomarkers for different diseases in the future and also as a marker of quality and safety in the quality control of blood products.
Keywords: blood products; extracellular membrane vesicles; krvni produkti; transfusion; transfuzija; zunajcelični membranski vezikli